Study of B→Xγ decays and determination of |Vtd/Vts| - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
Using a sample of 471×106 B¯¯¯B events collected with the BABAR detector, we study the sum of seven exclusive final states B→Xs(d)γ, where Xs(d) is a strange (nonstrange) hadronic system with a mass of up to 2.0 GeV/c2. After correcting for unobserved decay modes, we obtain a branching fraction for b→dγ of (9.2±2.0(stat)±2.3(syst))×10−6 in this mass range, and a branching fraction for b→sγ of (23.0±0.8(stat)±3.0(syst))×10−5 in the same mass range. We find B(b→dγ)B(b→sγ)=0.040±0.009(stat)±0.010(syst), from which we determine |Vtd/Vts|=0.199±0.022(stat)±0.024(syst)±0.002(th).